Effect of Education on Patient Colonoscopy Compliance: Literature Review - Sri Sulastri; Lia Natalia; Lastri Nainggolan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Bowel preparation is essential to ensure optimal visualization during colonoscopy, thus facilitating a safe procedure and ensuring comprehensive data acquisition. An important aspect of patient preparation is education, which is critical to ensure optimal outcomes and patient compliance.The purpose of this study is to analyze the effect of education on patient compliance in performing colonoscopy examination preparation in the endoscopy unit. The research method employed was a comprehensive literature review on patient compliance with colonoscopy preparation. A comprehensive search strategy was employed, encompassing three prominent web databases: Google Scholar, Proquest, and Gale. The search was conducted from 2016 to 2024, and the full-text articles were obtained in PDF format for further analysis. The search was conducted using the keywords